2022
DOI: 10.1038/s41598-022-05929-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of compounds to identify novel epigenetic regulatory factors that affect innate immune memory in macrophages

Abstract: Trained immunity and tolerance are part of the innate immune memory that allow innate immune cells to differentially respond to a second encounter with stimuli by enhancing or suppressing responses. In trained immunity, treatment of macrophages with β-glucan (BG) facilitates the production of proinflammatory cytokines upon lipopolysaccharide (LPS) stimulation. For the tolerance response, LPS stimulation leads to suppressed inflammatory responses during subsequent LPS exposure. Epigenetic reprogramming plays cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…Moreover, Ezh2 was one of the upregulated genes in macrophages with LPS tolerance found in our previous publication [ 43 ]. The screening of epigenetic inhibitors also demonstrated that the Ezh2 inhibitor enhances TNF-α expression in the LPS-tolerant macrophages [ 44 ]. Thus, the control of macrophage responses through the manipulations of epigenetics is interesting for controlling sepsis immune responses [ 13 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ezh2 was one of the upregulated genes in macrophages with LPS tolerance found in our previous publication [ 43 ]. The screening of epigenetic inhibitors also demonstrated that the Ezh2 inhibitor enhances TNF-α expression in the LPS-tolerant macrophages [ 44 ]. Thus, the control of macrophage responses through the manipulations of epigenetics is interesting for controlling sepsis immune responses [ 13 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same modifications of histone 3 were present in immune relevant gene locations in myeloid cells of humans and mice after induction of trained immunity [ 8 , 9 , 40 ]. The H3K27ac, H3K4me1 and H3K4me3 modifications were involved in the enhanced immune response in beta glucan-trained murine macrophages [ 10 ], while H3K4me3 and H3K27me3 histone modifications are associated with epigenetic regulation of human immune related genes [ 13 ]. In the current study, increased modifications of H3H3K4me1, H3K4me3 and H3K27ac and decreased modifications of H3K27me3 affected multiple pathways associated with bacterial phagocytosis by channel catfish myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Trained immunity in mice results from epigenetic reprogramming of monocytes and macrophages through acetylation or methylation of specific lysines in the histone-H3 [ 8 , 9 ]. These changes occur at promoter regions H3K4me3 [ 8 , 10 , 11 ], and H3K27ac [ 9 , 10 , 12 ], enhancer regions H3K4me1 [ 10 , 13 ] and polychrome repression or gene silencing H3K27me3 [ 14 ]. Beta glucan exposure can induce these modifications in mammals, via the dectin-1 receptor [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lysine methylation, a key, dynamic posttranslational modification that regulates protein stability and function, is regulated by lysine methyltransferase and lysine demethylase (95)(96)(97)(98). The abnormal expression of methyltransferase in many tumor types has been proven to be related to tumorigenesis and development, which has become the focus of anticancer research (98)(99)(100).…”
Section: Other Modificationsmentioning
confidence: 99%